Political Economy Of Balkans: Challenges And Perspectives - Ehlimana Spahić (Društvene i Humanističke Studije, 2018)
Reaffirmation of political economy as a subdiscipline of political science is based on the necessity of finding an adequate scientific and practical framework to overcome numerous challenges arising from the interaction between the political and economic system. Harmonized interaction of these two basic social systems is crucial for the successful functioning of each state. In this context, the author analyzed the capacity of the Balkan countries in achieving state stability, freedom of economy, competitiveness and quality of the business environment. Based on the analysis and the appropriate theoretical and conceptual frameworks of the political economy, the author offers adequate recommendations through which it is possible to improve the interaction between these two fundamental social systems.